Effect of reconstituted human apolipoprotein A-I on recurrent ischemic events in survivors of acute MI - Povsic, Thomas J.; Korjian, Serge; Bahit, M. Cecilia; Chi, Gerald; Duffy, Danielle; Alexander, John H.; Vinereanu, Dragos; Tricoci, Pierluigi; Mears, Sojaita Jenny; Deckelbaum, Lawrence I.; Bonaca, Marc; Ridker, Paul M.; et al. (Journal of the American College of Cardiology, 2024)
Background - The AEGIS-II trial hypothesized that CSL112, an intravenous formulation of human apoA-I, would lower the risk of plaque disruption, decreasing the risk of recurrent events such as myocardial infarction (MI) among high-risk patients with MI. - Objectives - This exploratory analysis evaluates the effect of CSL112 therapy on the incidence of cardiovascular (CV) death and recurrent MI. - Methods - The AEGIS-II trial was an international, multicenter, randomized, double-blind, placebo-controlled trial that randomized 18,219 high-risk acute MI patients to 4 weekly infusions of apoA-I (6 g CSL112) or placebo. - Results - The incidence of the composite of CV death and type 1 MI was 11% to 16% lower in the CSL112 group over the study period (HR: 0.84; 95% CI: 0.7-1.0; P = 0.056 at day 90; HR: 0.86; 95% CI: 0.74-0.99; P = 0.048 at day 180; and HR: 0.89; 95% CI: 0.79-1.01; P = 0.07 at day 365). Similarly, the incidence of CV death or any MI was numerically lower in CSL112-treated patients throughout the follow-up period (HR: 0.92; 95% CI: 0.80-1.05 at day 90, HR: 0.89; 95% CI: 0.79-0.996 at day 180, HR: 0.91; 95% CI: 0.83-1.01 at day 365). The effect of CSL112 treatment on MI was predominantly observed for type 1 MI and type 4b (MI due to stent thrombosis). - Conclusions - Although CSL112 did not significantly reduce the occurrence of the primary study endpoints, patients treated with CSL112 infusions had numerically lower rates of CV death and MI, type-1 MI, and stent thrombosis-related MI compared with placebo. These findings could suggest a role of apoA-I in reducing subsequent plaque disruption events via enhanced cholesterol efflux. Further prospective data would be needed to confirm these observations.